The Effects of Learning Al-Quran Hadits and Tadarus Activities on the Ability to Read the Al-Quran in Madrasah Tsanawiyah Students: Does the Mediation of Reading Intention Matter? - Handayani, Novi Listia; Prahara, Erwin Yudi; Daryono, Rihab Wit (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
This research aims to investigate the influence of Al-Quran Hadith learning and tadarus activities on students' Al-Quran reading ability as well as the mediating role of reading intention in the relationship between these two variables. The research method used was a quantitative approach with a survey method, involving 78 students at MTs Muhammadiyah 3 Yanggong as participants. The data collection technique was carried out using a Likert scale with four main variables: Al-Quran Hadith learning, tadarus activities, ability to read the Al-Quran, and reading intention. Data analysis was carried out using the PLS-SEM technique by testing the validity, reliability, and goodness-of-fit of the model. The research results show that reading intention has a positive and significant influence in improving students' ability to read the Quran. Meanwhile, learning the Quran and Hadith has an insignificant effect. Reading intention also mediates the relationship between tadarus activities and students' ability to read the Quran. The implications of this research highlight the importance of integrating spiritual values in learning the Quran, Hadith, and Tadarus. Teachers can use this research as a foundation for designing learning experiences that strengthen students' spiritual intentions and connect them to academic learning. Recommendations include Collaboration between schools, parents, and communities can be an important factor in strengthening students' reading intentions. Parents can provide support and encouragement to their children to read the Quran with good intentions, while communities can provide a supportive environment for religious practice. By implementing these recommendations, it is hoped that we can improve the balance between Al-Quran hadith learning, tadarus activities, and reading intention to develop and improve students' Al-Quran reading abilities.